The variant [ʃ] in the Spanish of Ciudad Juárez - Mendez, Luis Alberto (Borealis – An International Journal of Hispanic Linguistics, 2017)
A characteristic feature of the Spanish spoken in the Mexican state of Chihuahua is the pronunciation of the standard phoneme /tʃ/ (<ch>) as a non-standard allophone [ʃ] (<sh>). The present study analyzes the social and linguistic factors that influence variation in the Mexico-United States border community of Ciudad Juárez. Direct and indirect elicitations techniques were used to gather tokens of /tʃ/ from a sample of 40 local speakers who varied in age, sex, socioeconomic status, education level, and degree of bilingualism. The data was perceptually and acoustically interpreted and then statistically examined using variable rules analysis. On the linguistic side, the results show that [s], [i], [u] in preceding phonological context favor weakening. On the social side, the most prone participants to produce [ʃ] were: young men from low socioeconomic status, regardless of being Spanish monolinguals or Spanish-English sequential bilinguals. These findings indicate an ongoing gender shift with respect to previous research in the same community.